INI-1-Deficient Sinonasal Carcinoma: Case Report with Emphasis on Differential Diagnosis - Anwaar M. Alsayed; Eman A. Aljufairi; Amjad O. Alshammari; Khalid A. Alsindi; Omar A. Sabra (Hindawi Limited, 2022)
SMARCB1-deficient sinonasal carcinoma is a newly described entity, with less than 100 reported cases. It is characterized by basaloid or rhabdoid morphology and is diagnosed by complete loss of nuclear SMARCB1 (INI-1). The morphologic appearance, specific immunophenotypic markers, and unique molecular make-up distinguish this entity from other various malignant neoplasms. We present a case of a 55-year-old male that presented with a large progressing palatine mass. Magnetic resonance imaging showed a heterogeneous mass involving the left maxillary space. The initial biopsy was diagnosed as undifferentiated carcinoma. Resection was performed, and immunohistochemical studies revealed a complete loss of INI-1, refining the diagnosis to SMARCB1-deficient sinonasal carcinoma. Diagnosis of SMARCB1-deficient sinonasal carcinoma should be considered in all undifferentiated sinonasal carcinomas. Immunohistochemistry or molecular studies are mandatory to confirm the diagnosis and exclude other morphologically similar entities.